2021
DOI: 10.2196/26824
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Reality Game (The Secret Trail of Moon) for Treating Attention-Deficit/Hyperactivity Disorder: Development and Usability Study

Abstract: Background Attention-deficit/hyperactivity disorder (ADHD) affects between 4% and 8% of children worldwide. The treatment of choice is multimodal treatment. Multimodal interventions for ADHD may be improved by incorporating new treatments, such as treatment via serious video games. The Secret Trail of Moon (TSTM) is a virtual reality serious video game that was designed for cognitive training related to core ADHD symptoms and executive dysfunction. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 49 publications
0
55
0
1
Order By: Relevance
“…In addition, there is effectiveness with a medication-treated pediatric ADHD population and note of the need for pragmatic RCTs to build the evidence generation complemented by qualitative humancentered investigations [80]. An RCT tested the effectiveness of a serious video game (i.e., development and usability) and found that it may complement the current multimodal approach for treating ADHD [127].…”
Section: Immersive Technologiesmentioning
confidence: 99%
“…In addition, there is effectiveness with a medication-treated pediatric ADHD population and note of the need for pragmatic RCTs to build the evidence generation complemented by qualitative humancentered investigations [80]. An RCT tested the effectiveness of a serious video game (i.e., development and usability) and found that it may complement the current multimodal approach for treating ADHD [127].…”
Section: Immersive Technologiesmentioning
confidence: 99%
“… IDEAL-Games framework [ 22 ] adapted to create a general guide for game-based attention deficit hyperactivity disorder treatment. …”
Section: Ideal-games Frameworkmentioning
confidence: 99%
“…In our example, TSTM [ 21 ] was based on the models proposed by Russell Barkley [ 32 ] and Thomas Brown [ 33 ]. See Rodrigo-Yanguas et al [ 21 , 22 ] for a description of the general characteristics of TSTM.…”
Section: Ideal-games Frameworkmentioning
confidence: 99%
See 2 more Smart Citations